2013
DOI: 10.1038/ncomms2488
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced reading by training with imposed time constraint in typical and dyslexic adults

Abstract: Poor reading skills of developmental dyslexics persist into adulthood with standard remediation protocols having little effect. Nevertheless, reading improves if readers are induced to read faster. Here we show that this improvement can be enhanced by training. Training follows a multi-session procedure adapted to silent sentence reading, with individually set, increasingly more demanding, time constraints (letter-by-letter masking). In both typical and dyslexic adult readers, reading times are shortened and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 31 publications
4
96
2
Order By: Relevance
“…The persistence of reading disorders that lasts into adulthood, notwithstanding experience, has been moderately accredited to a decrease in brain malleability beyond childhood. In alignment with such view, research (Breznitz et al, 2013) significantly showed that corrective interventions could be less effective in adults. However, research proved that effective interventions could be effective in enhancing memory processes.…”
Section: Strategy Intervention Theorymentioning
confidence: 89%
See 1 more Smart Citation
“…The persistence of reading disorders that lasts into adulthood, notwithstanding experience, has been moderately accredited to a decrease in brain malleability beyond childhood. In alignment with such view, research (Breznitz et al, 2013) significantly showed that corrective interventions could be less effective in adults. However, research proved that effective interventions could be effective in enhancing memory processes.…”
Section: Strategy Intervention Theorymentioning
confidence: 89%
“…As such, interventions are significantly needed to support all learners with dyslexia. Breznitz et al (2013) indicated that readers with dyslexia in all school and university levels encounter reading impairments and difficulties which hinder their reading comprehension and reading accuracy and make them less accurate readers in comparison with their non-dyslexic peers. The persistence of reading disorders that lasts into adulthood, notwithstanding experience, has been moderately accredited to a decrease in brain malleability beyond childhood.…”
Section: Strategy Intervention Theorymentioning
confidence: 99%
“…Following several continuous successful trials, the program speeds the disappearance of letters from the screen, in an accelerated manner, tailored to the individual's reading pace [for more technical information see ]. The RAP has been shown to improve reading speed, and in some cases also accuracy, and comprehension in both children and adults with or without reading disabilities in several orthographies, including Hebrew (Horowitz- Kraus & Breznitz, 2011 ;Breznitz et al., 2013 ;, Horowitz-Kraus, 2015, English Niedo, Lee, Breznitz, & Berninger, 2014 ;Horowitz-Kraus, 2015 ; German (Korinth, Dimigen, Sommer, & Breznitz, 2009 ), and Dutch (Snellings, van der Leij, de Jong, & Blok, 2009 ). The benefi t of the RAP training is presumed to arise from a working-memory mechanism (Breznitz & Share, 1992 ;Niedo et al, 2014 ) as well as error-monitoring and attention abilities (Horowitz- .…”
Section: Plasticity Of Error Monitoring In Dyslexia and The Reading Amentioning
confidence: 96%
“…The Reading Acceleration Program (RAP) is a computerized reading intervention program that focuses on reading fl uency (Breznitz, Shaul, Horowitz-Kraus, Sela Nevat et al, 2013 ). The program manipulates letter presentation rate, requiring the participants to read at their self-paced rate, while monitoring reading comprehension.…”
Section: Plasticity Of Error Monitoring In Dyslexia and The Reading Amentioning
confidence: 99%
“…Long-term effects on reading or effects of transfer to reading without time constraints may be expected only after a considerable period of training (e.g., Breznitz et al, 2013;Snellings, van der Leij, de Jong, & Blok, 2009), particularly in children with reading experience of several years who have already established inefficient processes of reading. Nevertheless, the examination of different manipulations, which may facilitate reading on-line, is scarce.…”
Section: The Current Studymentioning
confidence: 99%